Potential Impact of Integrated Stigma Mitigation Interventions in Improving HIV/AIDS Service Delivery and Uptake for Key Populations in Senegal. (1st January 2017) - Lyons, Carrie E.; Ketende, Sosthenes; Diouf, Daouda; Drame, Fatou M.; Liestman, Benjamin; Coly, Karleen; Ndour, Cheikh; Turpin, Gnilane; Mboup, Souleymane; Diop, Karim; Toure-Kane, Coumba; Castor, Delivette; et al.
Abstract : Background: Men who have sex with men (MSM) and female sex workers (FSW) are consistently shown to have a higher burden of HIV compared with other adults in Senegal. This study, HIV Prevention 2.0, evaluates the impact of the 3-tiered integrated stigma mitigation interventions (ISMIs) approach to optimizing HIV service delivery for key populations in Senegal. Methods: Baseline assessment includes a questionnaire and biological testing for HIV. A proportion of participants enrolled into a 24-month longitudinal cohort with questionnaires and biological testing every 3 months. In these preliminary analyses, ISMIs are evaluated from participants in the cohort through uptake of HIV services and implementation outcomes. Results: Overall, 724 MSM and 758 FSW participated in the baseline assessment. HIV prevalence is 30.2% (n = 219/724) among MSM and 5.3% (n = 40/758) among FSW. Fear of seeking health services among MSM is 17.7% (n = 128/724) at baseline, 10.5% (n = 18/172) at month 3, and 9.8% (n = 10/102) at month 6 ( P < 0.004); and among FSW is 21.9% (n = 166/758) at baseline, 8.1% (n = 15/185) at month 3, and 10.7% (n = 18/168) at month 6 ( P < 0.001). Overall, 63.9% (n = 62/97) of MSM and 82.5% (n = 118/143) of FSW agreed that the intervention is effective in addressing stigma; however, loss to follow-up was 41.1% among MSM and 10% among FSW. Conclusion: Baseline data reinforce the need for stigma mitigation interventions, combined with enhanced linkage and retention to optimize HIV treatment. Preliminary results show high levels of HIV-related risk determinants and suggest the potential utility of the ISMI to decrease perceived stigma relating to engagement in HIV prevention, treatment, and care services among key populations in Senegal.